ICCE 2023 International Conference on Chinese Education / Assoc Prof Dr Hoe Foo Terng - Hoe, Foo Terng (Academy of Language Studies, 2024)
The theme of the conference was “承传中华，沟通世界” (Inherit the Chinese language and connect the world). The conference was co-organized by Universiti Tunku Abdul Rahman (UTAR), the Kedah State Education Department and the Organization of Taiwan Education and Cultural in Malaysia. The conference was held from November 17th to 19th, 2023, taking place at the Swiss Avenue Hotel in Sungai Petani, Kedah, and was conducted physically (face-to-face). The keynote speakers were Prof. Dato Dr. Lin Shuihao from UTAR and Dr. Zhang Jialin from the Department of Education at National Taiwan Normal University.